EXPLORING STUDENTS’ PERSPECTIVES ON GOOD AND EFFECTIVE ENGLISH TEACHER BASED ON GENDER DIFFERENCES - Warsini, Luh Mera; Artini, Luh Putu; Wahyuni, Ni Luh Gede Eka (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study explores the perceptions of male and female students regarding good and effective English teachers. The research involved the 8th grade students at SMP Negeri 4 Seririt, with 73 valid responses from 43 male students and 30 female students. The data collection methods included self-ranked questionnaires, open questionnaires, and focus group discussions. The findings revealed that male and female students have different perceptions of what makes a good and effective English teacher. Male students prioritized a teacher who cares about all students, while female students emphasized the importance of a teacher who understands the strengths and weaknesses of each student. Both male and female students agreed on the significance of a teacher who provides activities that arouse students' interest in learning English. The study concluded that an effective English teacher should possess pedagogic competence, professionalism, and the ability to support students in achieving their learning goals. The findings provide valuable insights for educators to understand and cater to the diverse perceptions of students in the learning environment.